2012
DOI: 10.4049/jimmunol.1200382
|View full text |Cite
|
Sign up to set email alerts
|

V(D)J Recombinase-Mediated TCR β Locus Gene Usage and Coding Joint Processing in Peripheral T Cells during Perinatal and Pediatric Development

Abstract: The generation of TCR proteins is the result of V(D)J recombinase-mediated genomic rearrangements at recombination signal sequences (RSS) in human lymphocytes. V(D)J recombinase can also mediate rearrangements at nonimmune or “cryptic” RSS in normal and leukemic human peripheral T cells. We previously demonstrated age- and gender-specific developmental differences in V(D)J coding joint processing at cryptic RSS within the HPRT locus in peripheral T cells from healthy children (Murray et al. 2006. J. Immunol. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 42 publications
2
18
1
Order By: Relevance
“…We have observed a progressive increase of TRB repertoire diversity and evenness during fetal development so that diversity at 22 to 26 WGA was indistinguishable from what was observed in healthy control infants. Together, our findings confirm and extend previous observations of nonrandom usage of TRAV and TRBV genes (46)(47)(48) and a slow increase in the extent of N nucleotide addition (45) and CDR-B3 length (28) during fetal development.…”
Section: Discussionsupporting
confidence: 91%
“…We have observed a progressive increase of TRB repertoire diversity and evenness during fetal development so that diversity at 22 to 26 WGA was indistinguishable from what was observed in healthy control infants. Together, our findings confirm and extend previous observations of nonrandom usage of TRAV and TRBV genes (46)(47)(48) and a slow increase in the extent of N nucleotide addition (45) and CDR-B3 length (28) during fetal development.…”
Section: Discussionsupporting
confidence: 91%
“…Studies by Murray et al have demonstrated genderspecific V(D)J recombinase-mediated TCRb gene usage and coding joint processing in human development that demonstrate direct effects on TCR diversity, though these studies were conducted on healthy children at a maximum age of 12.5 y. 63,64 In this study, these gender-specific differences in clonality did not occur across compartments -an observation that did occur with age-related associations, thus the strength of this gender-specific observation in NSCLC needs to be further evaluated in subsequent studies.…”
Section: E1051922-6 Volume 4 Issue 12 Oncoimmunologymentioning
confidence: 99%
“…Non-templated nucleotides are inserted by terminal deoxynucleotidyl transferase (TdT), and previous studies of its activity showed that insertion of nucleotides into coding junctions is not random [49, 50, 53]. A preference for G nucleotide insertions was observed during V(D)J recombination of plasmid substrates and in vivo , thus G/C nucleotides are present in coding junctions at higher levels than A/T nucleotides [50, 53].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we conducted an expanded frequency, clonality, and junctional processing analysis of illegitimate V(D)J deletion events at these loci during several stages of mouse development in wild-type animals. Results are discussed in the context of similar analyses of bona fide V(D)J rearrangements at the T cell receptor beta (TCRβ) locus and illegitimate events at the nonimmune HPRT1 locus found in human peripheral T cells that are not associated with T cell malignancies [49, 50]. …”
Section: Introductionmentioning
confidence: 99%